Legislative Ratio of Strengthening State Cyber and Cryptography Agencies in Law Enforcement: A Perspective of Legal System Theory - Rikmadani, Rd. Yudi Anton; Sudarti, Elly; Hafrida, Hafrida; Sutoto, Sukamto (Indonesian Journal of Advanced Research, 2024)
This research aims to address cyber threats and crimes in Indonesia. Currently, the responsibility for the implementation of cyber security tasks and functions is handled by the State Cyber and Cryptography Agency (BSSN). This situation makes it very difficult for BSSN to operate if its duties, functions, and authorities in cybercrime law enforcement are only regulated through a Presidential Regulation. This study uses a normative juridical method with a legislative approach that examines norms related to the authority of investigative institutions in law enforcement against cyber crimes. These findings highlight that there were 24.6 million cyberattacks recorded from January 1 to September 7, 2022, which caused losses to the community. The existence of BSSN was formed by the President through Presidential Regulation Number 28 of 2021 concerning the State Cyber and Cryptography Agency in carrying out its duties and authority to overcome cybercrime in the face of obstacles. This requires a comprehensive legal due diligence strategy that can be adjusted to legal compliance and potential legal problems of cybercrime. The results of the study show that to ensure security, justice, and legal certainty in the enforcement of cybercrime law can be carried out properly, it is necessary to have special laws and regulations that regulate cybercrime, with the existence of institutions that will implement laws and regulations in special law enforcement to deal with cybercrime, by containing legal compliance based on the applicable national legal system.